Sanksi Terhadap Pelaku Kekerasan Pada Anak Yang Mengakibatkan Luka Berat - Meli Dwi Anggraini; Siti Zailia; Armasito Armasito (Muqaranah, 2023)
Recently there has been frequent violence against children which of course violates children's rights. Various types of violations against violence against children seem to assume that children do not have rights to be protected. The main problem of this research is how to study Islamic law and positive law against sanctions on juvenile crimes that result in serious injuries in Decision Number: 1961/Pid.Sus/2016/PN .Plg. The purpose of this research is to examine the sanctions for perpetrators of crimes against children both in terms of Islamic law and positive law. The type of research used is literature (library research) which is analyzed using descriptive analysis techniques. The approach method is comparative, namely comparing Islamic law and positive law regarding sanctions for perpetrators of child crimes. The results of this study reveal that the judge's considerations in convicting criminals against perpetrators of violence against children who cause serious injuries in Decision Number: 1961/Pid.Sus/2016/PN .Plg. That is, the judge has first considered the facts at trial. In Islamic criminal law, criminal acts are punished with ta'zir, that is, in accordance with the actions and the decision is left to the ruler's policy or law. The difference between the two laws is that the witness imposed on the perpetrators of abuse according to law number 13 of 2014 is in the form of imprisonment, whereas in Islamic law it is in the form of qishas, diyat and ta'zir punishments.